Implementasi Automatic Speech Recognition Pada Penilaian Hafalan Al-Quran Dengan Metode Muroja’ah Berbasis Android - Alun Sujjada; Gina Purnama Insany; Muhamad Fajar Nugraha (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2024)
This research implements Automatic Speech Recognition (ASR) technology in the process of assessing Al-Qur'an memorization to overcome the problem of the increasing number of people who cannot read the Al-Qur'an fluently. With ASR, computers can recognize and transcribe human speech accurately, thereby improving the quality and accuracy of pronunciation and providing constructive feedback to learners. An Android-based application that uses the ASR service from the Google Speech API allows users to recite verses from the Koran and automatically recognize and evaluate what they have memorized. The hope is that the use of ASR technology can improve the ability to memorize the Al-Qur'an more effectively and flexibly without requiring direct teacher assistance. This system was developed using the Rapid Application Development (RAD) method with Blackbox Testing.